Diabetes mellitus as a vaccine-effect modifier: a review. (3rd May 2020) - Verstraeten, Thomas; Fletcher, Mark A.; Suaya, Jose A.; Jackson, Sally; Hall-Murray, Cassandra K.; Scott, Daniel A.; Schmöle-Thoma, Beate; Isturiz, Raul E.; Gessner, Bradford D.
ABSTRACT: Introduction: Diabetes mellitus (DM) is a highly prevalent, chronic condition in adults worldwide. Little is known about the potential role of diabetes as an effect modifier of vaccine protective responses. Areas covered: We conducted a literature review of the immunogenicity, efficacy and effectiveness of immunization in individuals, in studies that compared subjects with DM (DM+) and without DM (DM-). We found few published studies, which were only for vaccines against hepatitis B, influenza, pneumococcal disease, or varicela zoster. Except for a consistent attenuation of the immune response to hepatitis B vaccine among DM+ individuals, we found little other consistent evidence for DM as an effect modifier of vaccine responses. Expert opinion: There are substantial gaps in our knowledge of the impact of DM on the immune response to immunization or effect of vaccination.